Literacy Practices of Vocational Engineering Pre-Teachers in Surveying and Mapping. - Rahmawati, Anis (Pertanika Journal of Social Sciences & Humanities)
Surveys carried out in some countries show that more than half of labours have inadequate literacy skills to work in environments with knowledgeable society. Hence, as an institution orientating to workforce supply, vocational education is expected to instil a habit of literacy practice, which will encourage the improvement of graduates' literacy competence. This study aims to discuss literacy practice in vocational engineering education, which supports the mastery of engineering literacy. In this research, literacy practices focus in the surveying and mapping fields. This study was carried out using semi-structured interview. Participants in this study were three tutors were from the Vocational Engineering Education Department. Data collected were results of the interviews, students' fieldwork reports, and field observation. Findings from this study indicated that a habit of reading manuals or standards in engineering was considered low. Meanwhile, handwriting literacy habit was rare. Moreover, practical students tended to make detailed engineering design using computer applications. Communication ability to transfer information and ideas related to the results of vocational works was good, supported with technology-based presentation media..